2019
DOI: 10.1093/mnras/stz1204
|View full text |Cite
|
Sign up to set email alerts
|

Linear bias forecasts for emission line cosmological surveys

Abstract: We forecast the linear bias for Hα-emitting galaxies at high redshift. To simulate a Euclid-like and a WFIRST-like survey, we place galaxies into a large-volume dark matter halo lightcone by sampling a library of luminosity-dependent halo occupation distributions (HODs), which is constructed using a physically motivated galaxy formation model. We calibrate the dust attenuation in the lightcones such that they are able to reproduce the Hα luminosity function or the Hα cumulative number counts. The angle-average… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 106 publications
(202 reference statements)
11
34
0
Order By: Relevance
“…This behaviour is typically seen in the models when galaxies are selected by their star formation rate instead of a property that correlates more closely with stellar mass (Contreras et al 2013;Cowley et al 2016;Jiménez et al 2019). More recently Gonzalez-Perez et al (2018) found similar behaviour for the HOD of emission-line galaxies selected by the colour-magnitude cuts that will be used by the DESI emission-line galaxy survey (see also Merson et al 2019 andGonzalez-Perez et al 2020). The LRG population is dominated by central galaxies and contains a satellite fraction of f sat ∼ 0.10-0.04 in the redshift range = 0.6−1, where the mean number of satellites N s is close to a power law.…”
Section: S E L E C T I O N O F L U M I N O U S R E D G a L A X I E Smentioning
confidence: 69%
See 1 more Smart Citation
“…This behaviour is typically seen in the models when galaxies are selected by their star formation rate instead of a property that correlates more closely with stellar mass (Contreras et al 2013;Cowley et al 2016;Jiménez et al 2019). More recently Gonzalez-Perez et al (2018) found similar behaviour for the HOD of emission-line galaxies selected by the colour-magnitude cuts that will be used by the DESI emission-line galaxy survey (see also Merson et al 2019 andGonzalez-Perez et al 2020). The LRG population is dominated by central galaxies and contains a satellite fraction of f sat ∼ 0.10-0.04 in the redshift range = 0.6−1, where the mean number of satellites N s is close to a power law.…”
Section: S E L E C T I O N O F L U M I N O U S R E D G a L A X I E Smentioning
confidence: 69%
“…In the case of the most massive haloes, we extrapolate beyond the halo mass range of the HOD values; we do not have robust predictions for these haloes from the PMILL simulation due to its smaller volume compared to the GLAM boxes. This method was used recently by Merson et al (2019), where the authors extracted the HOD of H α galaxies from the GALACTICUS SAM catalogue (Benson 2012;Merson et al 2018), and used this to populate the Millennium-MXXL halo light-cone from Smith et al (2017).…”
Section: Galaxy Clustering In the Pmill And Glam Simulationsmentioning
confidence: 99%
“…The sky coverage is also 15000 deg 2 , and the expected number density of objects will ben g ≃ 2000 sources per deg 2 . We fit the number density distribution using the model 3 data by [76] and assume as galaxy bias redshift evolution b G ðzÞ ¼ 0.7 þ 0.7z, following the fitting for emission line object from [78]. For the tomography, we divide the survey in nine bins with the same redshift width (Δz ¼ 0.1), and the redshift accuracy is assumed to be σ z ¼ 0.001ð1 þ zÞ.…”
Section: Euclid-like Surveysmentioning
confidence: 99%
“…This yields as total number density of objectsn g ¼ 2039 sources per deg 2 , for which we introduce a 50% factor due to the Euclid completeness and purity. We assume a bias evolution function b g ðzÞ ¼ 0.7 þ 0.7z according to the fitting for Hα emission line object from [25]. The redshift accuracy is characterized by a dispersion σ z ¼ 0.001ð1 þ zÞ.…”
Section: Euclid-like Spectroscopic Surveymentioning
confidence: 99%